Dissolution Kinetics of Thermally Dehydrated Colemanite in Perchloric Acid Solutions - KUBILAY, S.; YALCINKAYA, Z.; ALKAN, S.; SAVRAN, A. (Asian Journal of Chemistry, 2010)
In this study, the dissolution of thermally dehydrated colemanite in aqueous perchloric acid solutions was investigated in a batch reactor employing the parameters of solid to liquid ratio, particle size, temperature and acid concentration. It was found that the dissolution rate increased with increasing temperature and acid concentration, decreasing particle size and solid to liquid ratio. No important effect of stirring speed was observed. The dissolution kinetics of colemanite was examined according to heterogeneous and homogeneous reaction models and it was found that the dissolution rate was controlled by heterogeneous chemical reaction. The activation energy of the process was determined to be 41.07 kJ mol-1. The experimental data were tested by graphical and statistical methods and it was found that the following model best fit the experimental data 1 - (1-X)1/3 = 7.56 × 105 (Rp)-0.1076 × (CA)0.4629 × (S/L) - 0.2525 × e-4938.7/T × t